Implementasi Good Governance dalam Pelayanan Administrasi Publik Pada Kantor Camat Sungai Tabukan Kabupaten Hulu Sungai Utara: Studi Kasus pada Seksi Pelayanan, Perekonomian, & Kesejahteraan Sosial - Muliadi Hapani; Gazali Rahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the implementation of Good Governance principles—transparency, accountability, participation, effectiveness, efficiency, rule of law, and inclusivity—in public administration services at the Sungai Tabukan Sub-district Office, especially in the Service, Economy, and Social Welfare Section. The method used is a qualitative approach with a case study design through observation, in-depth interviews, and documentation of sub-district officials and service user communities. The data was analyzed through reduction, presentation, and conclusion drawn, and tested for validity by triangulation and member check techniques. The results of the study show that procedural transparency, compliance with SOPs, and administrative accountability mechanisms have been running relatively well, so that services such as SKKM, marriage recommendations, and population documents can be processed openly and can be traced. However, the limitations of human resources, facilities, and digital infrastructure cause the effectiveness and efficiency of services to still be conditional and depend on key actors. Community participation has been facilitated through forums and feedback channels, but it is still dominated by village intermediaries so that the direct involvement of residents is not optimal. In terms of the rule of law and inclusivity, services have been based on regulations and are non-discriminatory, although there are still inequality in access and speed of services between regions. The main supporting factors include leadership commitment, internal work culture, and the existence of SOPs, while inhibiting factors include limited human resources, facilities, and information systems that have not been integrated. It was concluded that the implementation of Good Governance in public administration services in Sungai Tabukan District has been running functionally, but has not been fully consolidated systemically. Therefore, it is necessary to strengthen policies through the digitization of services, increase the capacity of the apparatus, improve facilities, integrate data-based accountability and transparency systems, and expand citizen participation channels to realize more professional, fair, and sustainable public administration service.